ANTICANCER ACTIVITY OF ETHANOL EXTRACT OF YELLOW ROOT (Arcangelisia flava) ON HEPG2 HEPATOCELLULAR CANCER CELLS - Hanifah Yusuf; Marhami Fahriani; Cut Murzalina (Jurnal Kedokteran Hewan, 2022)
This study aimed to evaluate anticancer activity and apoptosis induction of ethanolic extract of Arcalengisia flava (AF) roots on HepG2 cancer cell lines. The AF roots were extracted by maceration using ethanol 80%. MTT assay method was used to evaluate the anticancer activity and the proliferation of HepG2 cells. Flow cytometry method was used to assess the induction of HepG2 cells apoptosis. This study showed that the IC50 of AF ethanol extract against HepG2 cells was 109.14 μg/ml. With IC50 treatment, the apoptosis assay showed a significant decrease in intact cells (80.10±1.7%) and a significant increase in early apoptosis (7.9±0.7%) and late apoptosis cells of HepG2 cancer cells (4.9±0.35%) compared to control cells. Moreover, the proliferation of HepG2 cells was declined significantly in 48 and 72 hours after treatment with IC50 (77.5±5.76% and 64.3±5.37%, respectively) and 2xIC50 of the extract (75.9±1.79% and 70.5±4.27%, respectively). This research suggests that the ethanolic extract of AF roots can potentially be used for hepatocarcinoma treatment.